The Impact of Climate Change on the Protection of Human Rights in Developing Countries - Wartini, Sri; Thontowi, Jawahir; ., Sefriani (KnE Social Sciences, 2023)
The paper is aimed to examine the impacts of climate change on the legal protection of human rights in developing countries. Climate change has already variedly affected human rights, such as the right to live, the right to food, the right to water, the right to health, the right to enjoy a healthy environment and the right to self-determination. The various kinds of human rights are disturbed by the impacts of climate change. Climate change affects all aspects of human life, including social, economic, and cultural rights. Developing countries are more vulnerable and suffering if compared to developed countries due to the impacts of climate change. The research aims to comprehensively examine the protection of human rights in developing countries due to the effects of global warming, examine the obstacles, and find solutions to the protection of human rights. The research is normative juridical research by employing conceptual and statutory approaches. The result of the study indicates that: first, climate change affects the protection of all human rights; second, the protection of human rights in developing countries due to the impacts of climate change needs the assistance of developed countries; third, there are some solutions to address the protection of human rights in developing countries. Keywords: Climate Change, Developing Countries, Impacts, Human Rights, Protection